Omics approaches and large-scale data analysis in ageing research 1 - Magalhães, João Pedro de (Henry Stewart Talks, 2017)
Key biogerontology questions, Molecular signature of ageing, Transcriptome sequencing, RNA-seq of ageing tissues and calorie restriction, Microarrays & Proteomics, Epigenetic changes with age, Other large-scale approaches, Approaches & challenges for data analysis, Functional enrichment, Adaptive responses to ageing, Plasticity of the ageing process, Human ageing genomic resources, GenAge database, The genome as the digital code of life, Genetic determinants of human longevity, The naked mole-rat genome resource, Sequencing the bowhead whale genome